Dl-3-n-Butylphthalide Alleviates Behavioral and Cognitive Symptoms Via Modulating Mitochondrial Dynamics in the A53T-α-Synuclein Mouse Model of Parkinson’s Disease - Li, Huiying; Wang, Hongquan; Zhang, Ling; Wang, Manshi; Li, Yanfeng (Frontiers in Neuroscience, 2021)
Background: Aggregation and neurotoxicity of the presynaptic protein α-synuclein and the progressive loss of nigral dopaminergic neurons are believed to be the key hallmarks of Parkinson’s disease (PD). A53T mutant α-synuclein causes early-onset PD and more severe manifestations. A growing body of evidence shows that misfolding or deposition of α-synuclein is linked to the maintenance of mitochondrial dynamics, which has been proved to play an important role in the pathogenesis of PD. It has been observed that Dl-3-n-butylphthalide (NBP) may be safe and effective in improving the non-tremor dominant PD. However, the potential mechanism remains unclear. This study aimed to investigate whether NBP could decrease the loss of dopaminergic neurons and α-synuclein deposition and explore its possible neuroprotective mechanisms. Methods: A total of 20 twelve-month-old human A53T α-synuclein transgenic mice and 10 matched adult C57BL/6 mice were included into study; 10 adult C57BL/6 mice were selected as the control group and were administered with saline (0.2ml daily for 14days), 20 human A53T α-synuclein transgenic mice were randomly divided into A53T group (treated in the same manner as in the control group) and A53T+NBP group (treated with NBP 0.2ml daily for 14days). Several markers of mitochondrial fission and fusion and mitophagy were determined, and the behavioral, olfactory, and cognitive symptoms were assessed as well. Results: In the present study, it was observed that the A53T-α-synuclein PD mice exhibited anxiety-like behavioral disturbance, impairment of coordination ability, memory deficits, and olfactory dysfunction, loss of dopaminergic neurons, and α-synuclein accumulation. Meanwhile, the mitofusin 1 expression was significantly decreased and the mitochondrial number and dynamin-related protein 1, Parkin and LC3 levels were increased. The detected levels of all markers were reversed by NBP treatment, and the mitochondrial morphology was partially recovered. Conclusion: In the present study, a valuable neuropharmacological role of NBP has been established in A53T-α-synuclein PD mouse model. The possible neuroprotective mechanisms may be that NBP is involved in the maintenance of mitochondrial dynamics including mitochondrial fission and fusion, and clearance of damaged mitochondria. It is essential to perform further experiments to shed light on the precise mechanisms of NBP on mitochondrial homeostasis.